Prophetic Ethics In Hadith Tolerance As The Moral Foundation Of Muslims In Digital Interactions - Muhammad Farizal Amri (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study explores Prophetic Ethics in Hadith Tolerance as the moral foundation for Muslims’ digital interactions, highlighting the relevance of prophetic moral values in shaping ethical online behavior. In an era characterized by rapid communication and moral fragmentation, the Prophet Muhammad’s teachings, embodied in the hadiths of rahmah (compassion), tasamuh (tolerance), hikmah (wisdom), and musyawarah (deliberation), offer a timeless ethical framework for guiding digital civility. Using a qualitative-descriptive approach through library-based content analysis, this research examines canonical hadith compilations (Sahih al-Bukhari, Sahih Muslim, Sunan Abu Dawud, Jami’ al-Tirmidhi, and Musnad Ahmad) and relevant classical commentaries to derive thematic moral categories and contextualize them within the ethics of digital communication. The findings reveal that the Prophet’s ethical model integrates emotional, intellectual, and social dimensions of morality: rahmah promotes digital empathy, tasamuh nurtures respect for diversity, hikmah cultivates reflective and responsible communication, and musyawarah encourages collaborative dialogue and consensus-building in digital spaces. Together, these principles form the “Prophetic Digital Ethics Framework,” an integrative moral paradigm that transforms online engagement into an arena of mercy, respect, and justice. This study contributes theoretically to Islamic moral scholarship by recontextualizing hadith ethics in digital life and practically by offering ethical guidance for fostering digital civility among Muslims in the contemporary era.